Linagliptin Ameliorates Methylglyoxal-Induced Peritoneal Fibrosis in Mice. - Takuo Nagai; Shigehiro Doi; Ayumu Nakashima; Taisuke Irifuku; Kensuke Sasaki; Toshinori Ueno; Takao Masaki (PLoS ONE, 2016)
Recent studies have reported increases of methylglyoxal (MGO) in peritoneal dialysis patients, and that MGO-mediated inflammation plays an important role in the development of peritoneal fibrosis through production of transforming growth factor-β1 (TGF-β1). Linagliptin, a dipeptidyl peptidase-4 inhibitor, exerts anti-inflammatory effects independent of blood glucose levels. In this study, we examined whether linagliptin suppresses MGO-induced peritoneal fibrosis in mice. Male C57/BL6 mice were divided into three groups: control, MGO injection plus saline, and MGO injection plus linagliptin (n = 6 per group). Peritoneal fibrosis was induced by daily intraperitoneal injection of saline containing 40 mmol/L MGO for 21 days. Saline was administered intraperitoneally to the control group. Linagliptin (10 mg/kg) or saline were administrated by once-daily oral gavage from 3 weeks before starting MGO injections. Immunohistochemical staining revealed that linagliptin suppressed expression of α-smooth muscle actin and fibroblast-specific protein-1, deposition of type I and III collagen, and macrophage (F4/80) infiltration. Peritoneal equilibration testing showed improved peritoneal functions in mice treated with linagliptin. Peritoneal injection of MGO increased plasma levels of glucagon-like peptide-1 (GLP-1) in mice, and a further increase was observed in linagliptin-treated mice. Although MGO increased plasma glucose levels, linagliptin did not decrease plasma glucose levels. Moreover, linagliptin reduced the TGF-β1 concentration in the peritoneal fluid of MGO-treated mice. GLP-1 receptor (GLP-1R) was expressed in monocytes/macrophages and linagliptin suppressed GLP-1R expression in MGO-injected mice. These results suggest that oral administration of linagliptin ameliorates MGO-induced peritoneal fibrosis.